PENGARUH BIAYA PENDIDIKAN DAN FASILITAS PENDIDIKAN TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI PESERTA DIDIK SMA BUKIT ASAM TANJUNG ENIM - Jaka Setiawan; Riswan Jaenudin; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
The problems of this reasearch are (1) whether there is influence to the educating cost on the learning outcomes of economics lesson learners, (2) whether there is influence to the educational facilities on economics subjects learners, and (3) whether there is influence of both on the learning outcomes of the students of economics subjects. The population of this research is the students of class X SMA Bukit Asam Tanjung Enim, comprising 171 students. It uses the Kerjcie Table sothat 118 samples are obtained. The tecnique of data collection uses the methods of documentation, observation and questionnaires. This documentation is used to see the learning result of students, observation used to know the facilities owned by the schools, and distribution of questionnaires to determine the effects the cost of education and educational facilities on learning outcomes. The results of reasearch showed that (1) there is influence caused by the cost of education on learning outcomes of economics subjects in high school learners Bukit Asam. from the calculations, it is obtained that the F count> F table atau75,97> 3.92, (2) there is significant influence of educational facilities to the learning outcome, and proved from the calculations : the F count> F table or 59.09> 3.92, and (3) there is simultaneous influence of both the cost of education and educational facilities to the learning outcomes, as indicated by the following calculations, the F count> F table, or 49.174> 3.92.